JOB SATISFACTION AND ITS PREDICTIVE MEASURES ON JOB SATISFACTION OF ADMINISTRATIVE STAFF IN SOUTH WEST NIGERIA UNIVERSITIES - Olorunsola E.O. (European Scientific Journal, ESJ, 2013)
﻿The study examined the components of job satisfaction and its predictive measures on job satisfaction of administrative staff in south west Nigeria Universities. The study employed a descriptive research of the survey type to describe and interpret the components of job satisfaction of administrative staff in the South West Nigeria Universities. A self constructed questionnaire tilted job satisfaction questionnaire (JSQ) was used to collect information from respondents. Four hundred respondents from various departments were rated by their heads of department. Multi stage technique was used in selecting the four Universities, two federal and two state Universities. The data were analyzed using multiple regression model. The study revealed that achievement is the best predictor of job satisfaction of administrative staff with a beta weight of 1.236. Recommendations were made based on the findings that the administrators and management of the Universities should give attention and priority to those variables that would promote job satisfaction among the administrative staff of the Universities. Since a person’s achievement, could advertise his personality in the society, the administrative policies should be enriching to accommodate in-service training on the job, car and housing loan, medical facilities, and if pension scheme is robust, security of the workers are ensured, the moderate job satisfaction could be high satisfaction.